2019
DOI: 10.1080/26395940.2019.1577702
|View full text |Cite
|
Sign up to set email alerts
|

Activation of persulfate by manganese oxide-modified sludge-derived biochar to degrade Orange G in aqueous solution

Abstract: Manganese oxide-loaded sludge-derived biochar (Mn-SDBC) was synthesized and used to activate persulfate (PS) for Orange G (OG) degradation. X-ray fluorescence and Fourier transform infrared spectroscopy analysis indicated that the manganese oxides were successfully loaded on the SDBC. The result of batch experiments suggests that OG can be efficiently degraded by PS activated by Mn-SDBC. Metal loading rate, biochar dosage and PS concentration play a crucial role in experiments, whereas pH has a minor effect on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…However, since the sludge is composed of other metals in addition to iron, these may also be acting in the persulfate activation process. Fan et al [33] and Hoa et al [31] found that PS can also be activated by manganese, aluminum, zinc, and copper, all of which are present in the red mud.…”
Section: Catalyst Optimal Conditions Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, since the sludge is composed of other metals in addition to iron, these may also be acting in the persulfate activation process. Fan et al [33] and Hoa et al [31] found that PS can also be activated by manganese, aluminum, zinc, and copper, all of which are present in the red mud.…”
Section: Catalyst Optimal Conditions Resultsmentioning
confidence: 99%
“…With the pH tests, it was also found that, with the course of the reaction, regardless of the initial pH, the pH of the medium decreased. This can be justified by the reaction of the sulfate radical with OH − and the consequent formation of H + , as represented in Equation ( 9) and mentioned by Fan et al [33].…”
Section: Homogenous Catalysismentioning
confidence: 99%
“…Using a modified method from Fan et al [25], corn cob was first cleaned with tap water, chopped into small pieces, dried at 100°C for 24 h in an oven, and pyrolyzed at 400°C for 4 h without oxygen. The produced biochar was then crushed to pass through a 35-mesh sieve.…”
Section: Biochar and Manganese Oxide-loaded Biochar (Mnox-biochar) Pr...mentioning
confidence: 99%
“…Carbon-based materials such as activated carbon and biochar can act as electron donors for persulfate to form sulfate radicals [24]. Biochar modified with manganese oxide was successfully applied to increase the persulfate oxidation efficiency [25]. In addition to being used as catalysts, manganese oxide and biochar were also employed as pollutant adsorbents.…”
Section: Introductionmentioning
confidence: 99%
“…The continuous flow UV/PS/ZVI process has not been previously studied; there is scarce information in the literature regarding the application of persulfate oxidation in a continuous-flow mode in general. According to a study by Fan et al, continuous flow persulfate oxidation was utilized to successfully degrade Orange G in an aqueous solution, where biochar made from sludge and linked with manganese oxide was used to activate persulfate [60]. The authors reported that the increase in PS concentration from 1 to 5 mM promoted the dye degradation; however, a further increase did not lead to significant change as excessive PS saturated the activation sites.…”
Section: Optimization Of the Continuous Flow Uv/ps/zvi Processmentioning
confidence: 99%